2018
DOI: 10.5713/ajas.14.0611
|View full text |Cite
|
Sign up to set email alerts
|

Fiber source and inclusion level affects characteristics of excreta from growing pigs

Abstract: ObjectiveThe objective of the study was to determine the influence of varying fibrous diets on fecal characteristics of growing pigs.MethodsA total of 104 pigs (initial weight 18±2.0 kg) were used in the study. They were housed in individual pens and fed on diets containing maize cob, grass hay, lucerne hay, maize stover, and sunflower husk. These fibers were included at 0, 80, 160, 240, 320 and 400 g/kg. Fecal and urine samples were collected.ResultsFecal output was largest amongst pigs fed on diets containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Low diarrhoea rates in pigs fed diets supplemented with PMS may be due to cellulose nutrient function as well as the enzymes produced during microbial fermentation. It was reported that increasing dietary fibre content could reduce duration and severity of diarrhoea after piglets weaning (Yu et al, 2016;Mpendulo et al, 2018). Longland (1993) also reported that piglets had almost no obvious diarrhoea by adding wood cellulose (Solka-floc; S; Brown & Co., Berlin, NH, USA) to the pre-weaning piglet diet, and this fact was confirmed in our study.…”
Section: Discussionsupporting
confidence: 85%
“…Low diarrhoea rates in pigs fed diets supplemented with PMS may be due to cellulose nutrient function as well as the enzymes produced during microbial fermentation. It was reported that increasing dietary fibre content could reduce duration and severity of diarrhoea after piglets weaning (Yu et al, 2016;Mpendulo et al, 2018). Longland (1993) also reported that piglets had almost no obvious diarrhoea by adding wood cellulose (Solka-floc; S; Brown & Co., Berlin, NH, USA) to the pre-weaning piglet diet, and this fact was confirmed in our study.…”
Section: Discussionsupporting
confidence: 85%
“…Effects of fiber source on nutrient digestibility and fiber fermentability in pigs depends on the physiochemical properties of various fiber-rich ingredients (Molist et al, 2014;Mpendulo et al, 2018). The different physiochemical characteristics of fiberrich ingredients also affects SCFA production in the gut of pigs.…”
Section: Energy and Fiber Digestibility In Diets Containing Common Fiber-rich Ingredientsmentioning
confidence: 99%
“…In a recent study, we evaluated tannins derived from chestnut and quebracho trees were evaluated for their capability to affect growth performance, blood metabolic profile, and faecal nitrogen concentration in post-weaned piglets [29]. Not surprisingly, we observed a higher fecal nitrogen excretion in tannin-fed piglets consistently with the known tannin property to form less digestible complexes with dietary proteins [30]. However, the performance of treated animals was comparable with that of controls, despite a very high dose of tannins administered.…”
Section: Introductionmentioning
confidence: 74%